2021
DOI: 10.1210/endocr/bqab248
|View full text |Cite
|
Sign up to set email alerts
|

Ribociclib Cytotoxicity Alone or Combined With Progesterone and/or Mitotane in in Vitro Adrenocortical Carcinoma Cells

Abstract: Mitotane is the only approved drug for the treatment of adrenocortical carcinoma (ACC). The regimen to be added to mitotane is a chemotherapy with etoposide, doxorubicin, and cisplatin. This pharmacological approach, however, has a limited efficacy and significant toxicity. Target-therapy agents represent a new promising approach to cancer therapy. Among these, a preeminent role is played by agents that interfere with cell cycle progression, such as CDK4/6-inhibitors. Here, we investigated whether ribociclib c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…TVBF-7 cells have already been used as an experimental cell model to test the efficacy of drugs proven effective in ACC, in addition to other ACC cell lines. Indeed, we demonstrated that progesterone receptors may be a druggable target in these ACC cells [35,36], thus confirming the correlation between the level of the progesterone receptor expression and the sensitivity of ACC cells to the cytotoxic effect elicited by progesterone [35,36,50,51]. Finally, the Cdk4/6 inhibitor ribociclib induces cytotoxicity and reduction of the cell proliferation rate in these cells, although the cell cycle perturbation appears to differ compared to other ACC cell lines.…”
Section: Tvbf-7supporting
confidence: 76%
See 4 more Smart Citations
“…TVBF-7 cells have already been used as an experimental cell model to test the efficacy of drugs proven effective in ACC, in addition to other ACC cell lines. Indeed, we demonstrated that progesterone receptors may be a druggable target in these ACC cells [35,36], thus confirming the correlation between the level of the progesterone receptor expression and the sensitivity of ACC cells to the cytotoxic effect elicited by progesterone [35,36,50,51]. Finally, the Cdk4/6 inhibitor ribociclib induces cytotoxicity and reduction of the cell proliferation rate in these cells, although the cell cycle perturbation appears to differ compared to other ACC cell lines.…”
Section: Tvbf-7supporting
confidence: 76%
“…Finally, the Cdk4/6 inhibitor ribociclib induces cytotoxicity and reduction of the cell proliferation rate in these cells, although the cell cycle perturbation appears to differ compared to other ACC cell lines. TVBF-7 cells accumulate, as expected, in G1 phase, while NCI-H295R cells and MUC-1 cells accumulate in G2 phase [36], thus supporting the experimental advantage to have different cell models that could reflect the different ACC behavior, both in vitro and in vivo. Interestingly, in line with the shared metastatic origin from patients in progression after EDP-M, the TVBF-7 cells reflect some, but not all, characteristics with the cell line MUC-1.…”
Section: Tvbf-7supporting
confidence: 72%
See 3 more Smart Citations